Investigation on the electrical performances of a 10 kV polymer insulator with surface moss deposition - Abd Rahman, Farah Asyikin (2018)
The polymer insulator is known for its superior insulation performance due to its hydrophobicity and has been widely used in power systems especially for distribution networks. In sustaining this upper hand status, several extensive studies have been undertaken in evaluating and investigating the relationship between hydrophobicity and the electrical performance of polymer insulator with pollution severity, weather and ultraviolet (UV) effects. For a tropical country such as Malaysia, the issue of the formation of moss deposited on the insulator surface as a part of pollution severity should be considered. In this study, a 10 kV polymer insulator was selected as a case subject with moss deposition on the surface. Its electrical performance was studied and compared with a clean polymer insulator through Maxwell and HFSS software simulation under both steady state and impulse voltage conditions. In addition to this study, both insulators were tested under different environmental conditions and voltage profiles in a fog chamber. The results showed that the deposited moss on the surface had a direct effect on the voltage breakdown values and that the moss can reduce the electrical stability of a power line especially a core contaminated polymer insulator under polluted air. These findings have significant implications for distribution network systems, especially in areas with a high probability of moss formation. It would be wise to take this information into account when designing any new line projects or improving existing networks by setting the proper insulation level.